Information Systems Scalability of the “Bolsa Família” Program: An Interpretative Case Study - de Antonio, Nadja Piedade; Fornazin, Marcelo; Santos, Rodrigo Pereira; Araujo, Renata Mendes (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
The Bolsa Família Program (PBF) is one of the largest income transfer programs in the world. One of its biggest challenges has been the scalability of this social program in a country with continental dimensions. Along with this challenge we have the scalability of the Information Systems (IS) that support the program operation. The scalability of PBF’s IS support comprises technology, people and processes in a very specific historical, political and organizational context.We aim to investigate how the scalability of IS that support PBF had evolved, based on a sociotechnical research approach. We discuss the execution and preliminary results of an interpretative case study aiming at describing and interpreting some very specific aspects of the technological support of PBF, something that has never been described before. As a contribution, we identified several factors, such as politics, technology and geography which are linked and have promoted the growth of CadÚnico (an IS that supports PBF) since its inception. We also aim to show how interpretative studies can help us learn about the relevance of studying non-technical and technical elements to understand IS in all their complexity in each context.